FORECASTING DEMAND FOR BUFFALO IN NORTH TORAJA DISTRICT, SOUTH SULAWESI PROVINCE - Lestari, Veronica S.; Rohani, St.; Rasyid, I. (Proceeding Buffalo International Conference, 2013)
Buffalo was used for traditional ceremonies namely Rambu Solo and Rambu Tuka. The purpose of this study was to forecast demand for buffalo in North Toraja regency in the short run. This study was conducted for a month in May 2013. Secondary data of buffalo quantity to be slaughtered for traditional ceremonies were collected from Central Statistics Bureau of North Toraja regency for three years since 2010 until 2012. Data were tabulated and then were calculated using linier trend. This study revealed that demand for buffalo in North Toraja Regency in the short run could be estimated using trend linier equation Yâ = 6,376 â 553.5 Xâ.